Developing and validating a nomogram for early predicting the need for intestinal resection in pediatric intussusception - Yu, Yuan-Yang; Zhang, Jia-Jie; Xu, Ya-Ting; Lin, Zheng-Xiu; Guo, Shi-Kun; Li, Zhong-Rong; Huang, Hui-Ya; Huang, Xiao-Zhong (Frontiers in Pediatrics, 2024)
Purpose Develop and validate a nomogram for predicting intestinal resection in pediatric intussusception suspecting intestinal necrosis. Patients & methods Children with intussusception were retrospectively enrolled after a failed air-enema reduction in the outpatient setting and divided into two groups: the intestinal resection group and the non-intestinal resection group. The enrolled cases were randomly selected for training and validation sets with a split ratio of 3:1. A nomogram for predicting the risk of intestinal resection was visualized using logistic regression analysis with calibration curve, C-index, and decision curve analysis to evaluate the model. Results A total of 547 cases were included in the final analysis, of which 414 had non-intestinal necrosis and 133 had intestinal necrosis and underwent intestinal resection. The training set consisted of 411 patients and the validation cohort included 136 patients. Through forward stepwise regression, four variables (duration of symptoms, C-reaction protein, white blood cells, ascites) were selected for inclusion in the nomogram with a concordance index 0.871 (95% confidence interval: 0.834–0.908). Conclusion We developed a nomogram for predicting intestinal resection in children with intussusception suspecting intestinal necrosis after a failed air-enema based on multivariate regression. This nomogram could be directly applied to facilitate predicting intestinal resection in pediatric intussusception suspecting necrosis.